2020
DOI: 10.1007/s10549-020-05739-7
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Same-Day Approach to Breast Reconstruction During the COVID-19 Crisis

Abstract: Purpose As our hospitals conserve and re-allocate resources during the COVID-19 crisis, there is urgent need to determine how best to continue caring for breast cancer patients. During the time window before the COVID-19 critical peak and particularly thereafter, as hospitals are able to resume cancer operations, we anticipate that there will be great need to maximize efficiency to treat breast cancer. The goal of this study is to present a same-day protocol that minimizes resource utilization to enable hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
115
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(117 citation statements)
references
References 36 publications
2
115
0
Order By: Relevance
“… 24 - 42 Nine studies fully met our inclusion criteria. 43 - 51 The flowchart of the process of study identification and selection is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 - 42 Nine studies fully met our inclusion criteria. 43 - 51 The flowchart of the process of study identification and selection is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We identified two case series, 49 , 51 three cross-sectional studies, 45 - 47 and four analytical cross-sectional studies. 43 , 44 , 48 , 50 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations have revealed that outpatient mastectomy is safe and feasible during this global pandemic and now is the time for both surgeons and patients to consider this as the surgical standard for appropriately selected patients. 8 …”
mentioning
confidence: 99%
“…Strategies have been quickly developed, during the 1 st wave, to screen cancer patients requiring medical treatment [18,19], overcome logistic barriers and adapt treatments to limit treatment-related immune deficiency and hospital visits and keep providing optimal breast cancer care. In particular, breast surgery has been often postponed in low-risk cancers [20] and temporarily substituted by preoperative endocrine therapy in Luminal disease [21], immediate reconstructions have been referred [22], hypofractionation has become more widely used, outside of the standard indications [23], weekly chemotherapy schedules have been converted to 3-weekly regimens and oral drugs more widely adopted [24,25], growth factors have been routinely added to avert long lasting G4 neutropenia [26]. Follow-up care for patients out of active treatment has been routinely moved from face to face to virtual visits [27,28] with global satisfaction [29].…”
mentioning
confidence: 99%